Bone morphogenetic protein-2 and -7 mediate the anabolic function of nucleus pulposus cells with discrete mechanisms. (2nd November 2017) - Leung, Victor Y. L.; Zhou, Lixiong; Tam, Wai-Kit; Sun, Yi; Lv, Fengjuan; Zhou, Guangqian; Cheung, Kenneth M. C.
ABSTRACT: Bone morphogenetic proteins (BMPs) play roles in promoting cell anabolism, especially in extracellular matrix production. The difference between BMP members in their capacity to modulate intervertebral disc cell activity is yet to be defined. BMP-7/OP-1 has been shown to retard disc degeneration. We compared the activity of BMP-7 with that of BMP-2 on nucleus pulposus (NP) cell phenotype and function, and investigated how they differentially affect the gene expression profiles of signaling cascade components in human NP cells under degenerative states. We found that while both BMP-2 and BMP-7 enhanced matrix production of bovine NP cells, BMP-7 is more potent than BMP-2 at various dosages (50–800 ng/ml). BMP-7 exerted a relatively stronger stimulation on sulfated glycosaminoglycan production and proliferation in human NP cells. Degenerated NP cells showed an overall weaker response to the BMPs than non-degenerated cells, and were more sensitive to BMP-7 than BMP-2 stimulation. Compared to BMP-2, BMP-7 not only induced the gene expression of canonical BMP components, but also evoked changes in MAPKs as well as CREB1 and EP300 gene expression in degenerated NP cells, suggesting potential activation of the cAMP dependent protein kinase related pathways. In contrast to BMP-2, BMP-7 concomitantly inhibited the expression of profibrotic genes. We propose that BMP-2 and BMP-7, and likely other BMPs, may operate multifaceted but discrete molecular machineries that give rise to their different capacity in regulating NP cell phenotype. Further investigations into such differential capacity may possibly derive alternative cues important for IVD repair or engineering.